In Response to Whyness - Hassan Fathzade (Journal of Philosophical Investigations, 2015)
In response to why-questions, we explain the phenomena, and the explanation is nothing but relating some phenomena to others, and at the end, projecting a comprehensive theory over the various phenomena. In this essay, we defend a unification approach to the knowledge and by introducing “reification of the word,” restrain prejudices.